1993
DOI: 10.1007/bf00593966
|View full text |Cite
|
Sign up to set email alerts
|

Posterior cranial fossa dimensions in the Chiari I malformation: Relation to pathogenesis and clinical presentation

Abstract: Skull dimensions were measured on lateral skull radiographs in 33 adult patients with MRI-verified Chiari I malformations and in 40 controls. The posterior cranial fossa was significantly smaller and shallower in patients than in controls. In the patients, there was a positive correlation between posterior fossa size and the degree of the cerebellar ectopia, which might indicate that a posterior cranial fossa which was originally too small had been expanded by the herniation of hindbrain structures at an early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
123
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(131 citation statements)
references
References 29 publications
2
123
1
5
Order By: Relevance
“…In recent times, however, several authors using x-ray, tomography and MRI examinations have also demonstrated that the posterior fossa volume, in the presence of BI and CM, is smaller than the observed in normal people [36][37][38][39] .…”
Section: Discussionmentioning
confidence: 96%
“…In recent times, however, several authors using x-ray, tomography and MRI examinations have also demonstrated that the posterior fossa volume, in the presence of BI and CM, is smaller than the observed in normal people [36][37][38][39] .…”
Section: Discussionmentioning
confidence: 96%
“…This reduced posterior fossa volume may in turn result in compression and herniation of the cerebellar tonsils. 6,13 Acquired CM-I has also been described in infants, particularly after lumbar puncture or placement of a lumboperitoneal shunt. 10 It should be noted that the first twin in the present study did undergo a lumbar puncture although only a small volume of cerebrospinal fluid was obtained for diagnostic purposes (< 1.5 ml); this .…”
Section: Discussionmentioning
confidence: 99%
“…1,8,10,12,28 It is likely that patients with CM-I have a reduced posterior fossa volume, which results in crowding at the foramen magnum. 6,21,25,27 Although cerebellar tonsil position is a convenient marker for crowding at the foramen magnum, the correlation is not exact. 26 In some cases, patients with < 5 mm of descent can have a clinical presentation of Chiari syndrome and even syringomyelia caused by crowding at the foramen magnum.…”
Section: Discussionmentioning
confidence: 99%